Pengaruh Struktur Modal dan Likuiditas terhadap ROA - Rahma, Nadya; Asih, Vemy Suci (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
This study aims to analyze the influence of capital structure with Debt To Equity Ratio (DER) proxy and Liquidity with Current Ratio (CR) proxy on Return On Assets (ROA) in Bank Negara Indonesia (BNI) for the 2016-2023 period both partially and simultaneously. This type of research is an associative quantitative research, using secondary data obtained in the form of a time series, the sample in this study is the quarterly financial statements of Bank Negara Indonesia (BNI) for the 2016-2023 period. The data analysis technique uses the Classical Assumptions and Multiple Linear Regression method. The results of this study show that Debt To Equity Ratio has a significant effect on Return On Assets, while Current Ratio does not have a significant effect on Return On Assets . Then, the results simultaneously showed that Debt To Equity Ratio  and Current Ratio  had a significant effect on Return On Assets.